2011
DOI: 10.1097/igc.0b013e3182150e98
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor-Factor VIIa Complex Induces Epithelial Ovarian Cancer Cell Invasion and Metastasis Through a Monocytes-Dependent Mechanism

Abstract: Our study suggested that the interaction between the TF-FVIIa complex might play a role in mediating EOC invasion and metastasis depending on MOs mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…have proposed that tumor cells might be activated by the macrophages and secrete angiogenic factors in head‐and‐neck squamous cell carcinomas . Our previous studies have certified TNF‐α expression upstream of IL‐8 expression in macrophage, when we added TNF‐α blocking antibody, IL‐8 expression was decreased . It has been reported that indirect interactions between tumor and stroma cells enhance the expression of angiogenic factors, such as IL‐1, and TNF‐α, in a conditioned medium, can increase IL‐8 expression.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…have proposed that tumor cells might be activated by the macrophages and secrete angiogenic factors in head‐and‐neck squamous cell carcinomas . Our previous studies have certified TNF‐α expression upstream of IL‐8 expression in macrophage, when we added TNF‐α blocking antibody, IL‐8 expression was decreased . It has been reported that indirect interactions between tumor and stroma cells enhance the expression of angiogenic factors, such as IL‐1, and TNF‐α, in a conditioned medium, can increase IL‐8 expression.…”
Section: Discussionmentioning
confidence: 80%
“…Interleukin‐13 (IL‐13) and IL‐4 can induce the differentiation of macrophages into M2 cells, with IL‐10 high and IL‐12 low phenotype. Our previous study have reported that coagulation factors II, III and XII induce the differentiation of peripheral blood monocytes from healthy women into M2‐like macrophages, and participate in promoting EOC progression . In our previous study, we have demonstrated that CD68 + macrophages are in close contact with CD31 + endothelial cells in peritoneum in the presence of EOC.…”
mentioning
confidence: 87%
“…CTCs accompany metastatic disease across all major types of carcinomas (Allard et al, 2004). Tumors have been shown to express TF in vivo , and TF expression has been shown to correlate with metastatic potential (Zacharski et al, 1983, 1986; Lee et al, 2011; Liu et al, 2011; Ma et al, 2011; Tian et al, 2011; Xu et al, 2011; Gil-Bernabe et al, 2012). Therefore, the process of hematogenous metastasis may present TF-expressing tumor cells to blood in the absence of a blood vessel injury.…”
Section: Ctc–blood Protein Interactionsmentioning
confidence: 99%
“…A database search revealed that PAR1 transcript levels are significantly higher in EOC tissues compared with those in normal ovarian tissues [37]. In addition, immune cells treated with TF-fVIIa complex potentially included in ascites can augment secretion of cytokines such as interleukin (IL)-8 (CXCL8), thereby increasing the motility and invasiveness of EOC cells [38]. EOC cells can secrete extracellular vesicles (EVs) associated with high levels of TF or TF-fVIIa associated with procoagulant activity, potentially leading to venous thromboembolism (VTE) [28,29,39].…”
Section: Potential Relationship Between Blood Coagulation and Inflmentioning
confidence: 99%